A Woman's Experiences in the Great War - Mack, Louise, 1870-1935 (Salt Lake City, UT : Project Gutenberg, 2011)
"A Woman's Experiences in the Great War" by Louise Mack is a historical account written in the early 20th century. The narrative chronicles the author's personal experiences as she travels to Belgium at the onset of World War I, focusing on her observations of the war's impact on the country and its people. The book not only provides a glimpse into the turmoil faced by civilians and soldiers alike but also highlights the bravery and resilience of individuals during this tumultuous period." "The opening of the work introduces us to the author's journey as she crosses the English Channel to Belgium amidst the backdrop of war. She encounters a Belgian captain who expresses his sorrow for the lost lives of soldiers, creating an emotional resonance from the start. Upon reaching Ostend, she observes the stark transformation of the once vibrant city into a place of desolation, complete with wounded soldiers and the impending threat of German forces. The narrative unfolds with vivid descriptions and personal reflections, emphasizing the urgency and peril of the situation as she navigates this new, dangerous landscape, setting the stage for her further adventures in Belgium." (This is an automatically generated summary.)
Release date is 2011-02-24
Produced by Andrea Ball & Marc D'Hooghe
Keywords: World War, 1914-1918 -- Personal narratives